Selenium-iron co-doped hydroxyapatite reinforced polylactic acid stent and preparation method thereof

By doping selenium and iron into HAP and adding PLLA/SF-HAP complex biological scaffolds prepared in PLLA, the problem of insufficient anti-tumor ability in osteosarcoma bone defect repair was solved, and effective tumor cell clearance was achieved and bone repair.

CN119424762APending Publication Date: 2025-02-14JIANGXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488479.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Polylactic acid (PLLA) biological scaffolds are insufficient in the repair of bone defects caused by osteosarcoma and cannot effectively remove residual tumor cells.

Method used

Selenium (Se) and iron (Fe) are doped into hydroxyapatite (HAP) by co-precipitation method to form selenium-ferric co-doped HAP (SF-HAP), which is then added to PLLA, by selecting PLLA/SF-HAP composite biological scaffold was prepared by sexual laser sintering technology.

Benefits of technology

This technical method effectively controls the release of Se and Fe ions, can promote bone repair and remove residual tumor cells in the bone defect environment, avoid tumor recurrence, and demonstrate good biocompatibility and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119424762A_ABST
    Figure CN119424762A_ABST
Patent Text Reader

Abstract

The invention discloses a selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and a preparation method thereof, and the preparation method comprises the following steps: co-doping SeO3 < 2-> and Fe < 3 + > into HAP through a co-precipitation method to obtain SF-HAP powder; sF-HAP and PLLA are dispersed in ethyl alcohol, and PLLA / SF-HAP composite powder is obtained through stirring, centrifuging, drying and the like; the PLLA / SF-HAP biological scaffold is prepared through an additive manufacturing technology, in order to endow the PLLA / HAP bone scaffold with an anti-tumor function, Fe is doped into HAP, a Fenton reaction can be promoted in an osteosarcoma environment so that ROS can be generated to kill tumor cells, but overexpressed GSH existing in the tumor cells can consume the ROS to weaken the anti-tumor effect, and doping of Se and Fe can reduce the crystallinity of HAP crystals, so that the anti-tumor effect is improved. The SeO3 < 2-> and the Fe < 3 + > are added into the tumor cells, so that the sustained release of functional ions is facilitated, meanwhile, the consumption of the SeO3 < 2-> and the Fe < 3 + > on the over-expressed GSH and H2O2 in the tumor cells can effectively destroy the redox balance in the tumor cells, and the death of the tumor cells is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biological scaffold preparation, in particular to a selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and a preparation method thereof. Background Art

[0002] Osteosarcoma is one of the most common primary malignant tumors, which is prone to deterioration and metastasis. At present, conventional treatments for osteosarcoma include surgical resection and adjuvant chemotherapy, but this will undoubtedly cause large bone defects. Hydroxyapatite (HAP) is usually used to prepare bone scaffolds because of its similar composition to human bone to induce bone regeneration. At the same time, polylactic acid (PLLA) is a biomedical material approved by the US Food and Drug Administration (FDA) with good biocompatibility, degradability and processability. It is enzymatically decomposed into carbon dioxide and water in the human body and excreted through urine. Therefore, combining PLLA and HAP is expected to promote bone regeneration. However, due to the lack of anti-tumor effect, its application in the repair of bone defects caused by osteosarcoma is greatly limited.

[0003] Fe 3+ It has good anti-tumor ability and can trigger the Fenton reaction with the overexpressed H2O2 in the tumor environment to produce ·OH (hydroxyl radical). ·OH is a highly toxic reactive oxygen species (ROS) that can cause oxidative damage to tumor cells. It is worth noting that the tumor environment also has overexpressed GSH (glutathione), which is an antioxidant that can protect tumor cells from oxidation by consuming ROS, thereby reducing Fe 3+ Therefore, before using ROS to kill tumor cells, it is urgent to solve the problem of GSH's consumption of ROS. 3+ When HAP is doped into PLLA bioscaffolds, it can promote osteogenesis in a bone tumor environment while the generated ROS can effectively kill residual tumor cells.

[0004] Trace element selenium (Se) is a trace element necessary for maintaining human health. As a common form of selenium, selenite (SeO3 2- ) can trigger the decomposition of overexpressed GSH in tumor cells to form superoxide anions (O2 ·- ), which can cause oxidative damage to tumor cells. At the same time, the low GSH level in normal cells will not trigger the production of high levels of ROS, which can undoubtedly protect normal cells from damage. Therefore, this ability to decompose GSH to produce ROS rather than just consume GSH makes Se a candidate for a new type of dynamic anti-tumor therapy. 3+In the present invention, Se and Fe elements are co-doped into HAP and finally introduced into PLLA, which can effectively control the release of Se and Fe ions in the tumor environment, thereby achieving the purpose of effectively eliminating osteosarcoma cells and promoting bone repair;

[0005] There is currently no report on using Se or Fe doped HAP and then introduced into PLLA scaffolds to produce ROS to kill tumor cells by decomposing GSH and H2O2 overexpressed in tumor cells. Summary of the invention

[0006] In order to solve the problem that the anti-tumor ability of polylactic acid (PLLA) biological scaffold is still insufficient when hydroxyapatite (HAP) is directly introduced into the PLLA biological scaffold, the present invention provides a selenium-iron co-doped hydroxyapatite reinforced PLLA scaffold and a preparation method thereof.

[0007] To achieve the above object, the present invention provides the following technical solution: a selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and a preparation method thereof, comprising the following steps:

[0008] S1. SeO3 is prepared by coprecipitation 2- and Fe 3+ Doped into hydroxyapatite (HAP) to obtain SF-HAP powder;

[0009] S2, dispersing PLLA powder in anhydrous ethanol to obtain a PLLA suspension, and then dispersing SF-HAP powder into the PLLA suspension to obtain a PLLA / SF-HAP mixed suspension, and subjecting the suspension to ultrasonication, magnetic stirring, centrifugation, drying, grinding and other steps to obtain a PLLA / SF-HAP composite powder;

[0010] S3. Prepare PLLA / SF-HAP scaffold by selective laser sintering technology using PLLA / SF-HAP composite powder.

[0011] Preferably, in step S1, preparing a synthetic HAP solution to obtain SF-HAP powder comprises the following steps:

[0012] S11, dispersing calcium nitrate pentahydrate in deionized water and ultrasonically treating it, adding polyethylene glycol to disperse it to prepare a calcium nitrate solution, stirring and reacting it at 60° C. for 30 minutes, and adding ammonia water to adjust the pH;

[0013] S12, dissolving diammonium hydrogen phosphate in deionized water, adjusting the pH with ammonia water and ultrasonically treating; slowly dropping the diammonium hydrogen phosphate solution into the calcium nitrate solution, stirring at 60° C. for 3 hours, taking the supernatant, repeatedly centrifuging and washing the solution with deionized water and ethanol, and drying the product in a vacuum oven to obtain HAP powder;

[0014] S13. The synthesis process of SF-HAP powder is as follows: in the above-mentioned process of synthesizing HAP, sodium selenite is additionally added to diammonium hydrogen phosphate, and ferric chloride is additionally added to calcium nitrate, and other reaction conditions remain unchanged, to finally obtain SF-HAP powder.

[0015] Preferably, in step S11, the molecular weight of the dispersant polyethylene glycol selected is 6000.

[0016] Preferably, in step S11, the alkaline pH of the solution is greater than 10.

[0017] Preferably, in step S1, the molar ratio of calcium nitrate to ferric chloride is in the range of 7:2-7:4.

[0018] Preferably, in step S13, the molar ratio of diammonium hydrogen phosphate to sodium selenite is in the range of 1:3-2:3.

[0019] Preferably, in step S2, the dispersion method is ultrasound and magnetic stirring, the ultrasonic dispersion time is 10-60 min, the temperature is 20-50°C; the magnetic stirring dispersion time is 0.5-6h, the speed is 300-800r / min, and the temperature is 30-60°C.

[0020] Preferably, in step S2, the particle size of PLLA is 0.1-5 um, and the purity is greater than 99%.

[0021] Preferably, in step S3, in the PLLA / SF-HAP bioscaffold, the mass fraction of SF-HAP is 5-30%, and the mass fraction of PLLA is 70-95%.

[0022] Preferably, in step S14, the weight of CuS@PMS is 5-30%, and the weight fraction of PCL is 70-95%.

[0023] Preferably, in step S3, the PLLA / SF-HAP composite powder is placed in a 3D printing system, and sintered layer by layer according to the slice information of the three-dimensional bracket model. The steps of preparing the bracket are: preheating the powder, spreading the powder with a roller, sintering the powder layer by layer with a laser beam, and removing excess powder after sintering to obtain a composite bracket. The process parameters of selective laser sintering are: laser power of 0.5-4W, scanning spacing of 0.2-1.0mm, scanning speed of 50-200m / s, and powder bed preheating temperature of 140-160℃.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] In the present invention, the present invention utilizes Fe 3+ and SeO32- The ion substitution process of HAP reduces the crystallinity of HAP, which is beneficial to the stable and continuous release of functional ions, thereby more effectively killing tumor cells in the long term.

[0026] The present invention adds SF-HAP into the PLLA matrix to prepare the composite biological scaffold, which is beneficial to Fe 3+ and SeO3 2- The sustained release of Fe 3+ Doped into HAP, it can react with H2O2 to produce ·OH, SeO3 2- Doped into HAP, it can effectively decompose GSH to generate O2 ·- .

[0027] The present invention uses selective laser sintering technology to prepare a composite biological scaffold with controllable porosity and personalized customization. Fe and Se elements are combined with HAP through ion substitution, and the structure is more stable.

[0028] The present invention utilizes the coprecipitation reaction process to convert SeO3 2- and Fe 3+ Doping into HAP reduces the crystallinity of HAP and promotes the stable release of functional ions. On the one hand, Fe 3+ It is possible to utilize the overexpressed H2O2 in the tumor environment to produce ·OH that can kill tumor cells. On the other hand, SeO3 2- Able to decompose the antioxidant GSH in the tumor environment and generate O2 ·- , expand oxidative stress, induce cell apoptosis, and finally the prepared PLLA / SF-HAP bioscaffold can remove residual tumor cells in the bone defect environment and avoid tumor recurrence. At the same time, this bioscaffold has good biocompatibility and degradability after implantation, and provides a three-dimensional space for cell survival and expansion, which is beneficial for cells to obtain sufficient nutrients and enable the cells to continue to grow in the scaffold, thereby achieving the purpose of bone repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the overall process of the present invention;

[0030] Figure 2 The ROS fluorescence staining images of tumor cells cultured on PLLA / HAP, PLLA / Fe-HAP, and PLLA / SF-HAP bioscaffolds in Example 1 after 1 day;

[0031] Figure 3 Figure 1 shows the content of GSH and H2O2 in tumor cells cultured on PLLA / HAP, PLLA / Fe-HAP, and PLLA / SF-HAP bioscaffolds for 1 day;

[0032] Figure 4 These are live and dead staining images of MG-63 cells in Example 1 after being cultured on PLLA / HAP, PLLA / Fe-HAP, and PLLA / SF-HAP bioscaffolds for one day. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Example 1, please refer to Figure 1-4 , the present invention provides a technical solution: a selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and a preparation method thereof;

[0035] SF-HAP nanoparticles were synthesized by chemical coprecipitation method. Ca(NO3)2, (NH4)2HPO4, FeCl3 and Na2SeO3 were donors of Ca, P, Fe and Se, respectively. Firstly, a mixed solution (Ca+Fe) of Ca(NO3)2 (0.5M) and FeCl3 (0.2M) was prepared by vigorous stirring at 60°C using polyethylene glycol (PEG, 0.2g) as dispersant. During the reaction, the pH value was kept at around 11 by dripping ammonium hydroxide. Similarly, a mixed solution (P+Se) of (NH4)2HPO4 (0.3M) and Na2SeO3 (0.45M) was prepared. Subsequently, the (P+Se) solution was added dropwise to the (Ca+Fe) solution under vigorous stirring and stirring was continued for 3 hours. The precipitate was washed three times with deionized water and alcohol, dried and ground to obtain SF-HAP powder.

[0036] 19g PLLA powder was dispersed in 500mL anhydrous ethanol and ultrasonically treated for 1 hour at an ultrasonic temperature of 25°C to obtain a PLLA suspension; 1g SF-HAP powder was dispersed into the PLLA suspension, the ultrasonic dispersion time was 30 minutes, the magnetic stirring dispersion time was 3 hours, and the magnetic stirring time was 25°C to obtain a uniformly dispersed PLLA / SF-HAP mixed suspension; the mixture was centrifuged for 1 hour at a centrifugal speed of 1200r / min, the drying time was 24 hours, and the powder was ground and dried for 10 minutes to obtain a PLLA / SF-HAP composite powder.

[0037] The PLLA / SF-HAP composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold are as follows: preheating the powder to a temperature slightly lower than the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA / SF-HAP bioscaffold, recorded as 5wt% PLLA / SF-HAP, and the main process parameters are: laser power of 1.2W, scanning spacing of 0.4mm, scanning speed of 80m / s, spot diameter of 400mm, and powder bed preheating temperature of 150℃.

[0038] In this example, in the cell experiment, tumor cells were cultured on the PLLA / SF-HAP composite bioscaffold, and the ratio of live to dead cells was 1:99, with almost no survival, proving that it has a good anti-tumor effect. At the same time, using ROS fluorescence to stain it, it can be found that a large amount of ROS is produced.

[0039] In this example, the PLLA / SF-HAP scaffold consumed H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 50% decrease in the absorbance of MB at 663 nm.

[0040] In this example, the PLLA / SF-HAP scaffold consumed GSH to generate superoxide radicals after 2.5 hours, resulting in a 50% decrease in the absorbance of DPBF at 412 nm.

[0041] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 15%.

[0042] In this example, after immersion in simulated body fluid for 28 days, the Fe 3+ The release amount reaches 10%.

[0043] In this example, after immersion in simulated body fluid for 28 days, the SeO3 2- The release amount reached 14%.

[0044] Embodiment 2,

[0045] SF-HAP nanoparticles were synthesized by chemical coprecipitation method. Ca(NO3)2, (NH4)2HPO4, FeCl3 and Na2SeO3 were donors of Ca, P, Fe and Se, respectively. First, a mixed solution of Ca(NO3)2 (1 M) and FeCl3 (0.5 M) was prepared by vigorously stirring at 60°C with polyethylene glycol (PEG, 0.4 g) as a dispersant. During the reaction, the pH value was kept at around 11 by dropping ammonium hydroxide. Similarly, a mixed solution of (NH4)2HPO4 (0.6 M) and Na2SeO3 (1 M) was prepared. Subsequently, the (P+Se) solution was added dropwise to the (Ca+Fe) solution under vigorous stirring. Then, the obtained solution was stirred for 3 hours. The aged precipitate was centrifuged three times with deionized water and alcohol, dried, and finally ground and sieved to obtain SF-HAP powder.

[0046] 18g PLLA powder was dispersed in 500mL anhydrous ethanol and ultrasonically treated for 1 hour at an ultrasonic temperature of 25°C to obtain a PLLA suspension; 2g SF-HAP powder was dispersed into the PLLA suspension, the ultrasonic dispersion time was 30 minutes, the magnetic stirring dispersion time was 3 hours, and the magnetic stirring time was 25°C to obtain a uniformly dispersed PLLA / SF-HAP mixed suspension; and then centrifuged for 1 hour at a centrifugal speed of 1200r / min, a drying time of 24 hours, and a powder grinding and drying time of 10 minutes to obtain a PLLA / SF-HAP composite powder.

[0047] The PLLA / SF-HAP composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold are as follows: preheating the powder to a temperature slightly lower than the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA / SF-HAP bioscaffold, recorded as 10wt% PLLA / SF-HAP, and the main process parameters are: laser power of 1.2W, scanning spacing of 0.4mm, scanning speed of 80m / s, spot diameter of 400mm, and powder bed preheating temperature of 150℃.

[0048] In this example, in the cell experiment, tumor cells were cultured on the PLLA / SF-HAP composite bioscaffold, and the ratio of live to dead cells was 1:99, with almost no survival, proving that it has a good anti-tumor effect. At the same time, using ROS fluorescence to stain it, it can be found that a large amount of ROS is produced.

[0049] In this example, the PLLA / SF-HAP scaffold consumed H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 55% decrease in the absorbance of MB at 663 nm.

[0050] In this example, the PLLA / SF-HAP scaffold consumed GSH to generate superoxide radicals after 2.5 hours, resulting in a 55% decrease in the absorbance of DPBF at 412 nm.

[0051] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 20%.

[0052] In this example, after immersion in simulated body fluid for 28 days, the Fe 3+ The release amount reaches 15%.

[0053] In this example, after immersion in simulated body fluid for 28 days, the SeO3 2- The release amount reached 19%.

[0054] Embodiment 3,

[0055] SF-HAP nanoparticles were synthesized by chemical coprecipitation method. Ca(NO3)2, (NH4)2HPO4, FeCl3 and Na2SeO3 were donors of Ca, P, Fe and Se, respectively. First, polyethylene glycol (PEG, 0.6 g) was used as a dispersant to prepare a mixed solution of Ca(NO3)2 (1.5 M) and FeCl3 (0.8 M) at 60°C with vigorous stirring. During the reaction, the pH value was kept at around 11 by dropping ammonium hydroxide. Similarly, a mixed solution of (NH4)2HPO4 (1.2 M) and Na2SeO3 (1.5 M) was prepared. Subsequently, the (P+Se) solution was added dropwise to the (Ca+Fe) solution under vigorous stirring. Then, the obtained solution was stirred for 3 hours. The aged precipitate was centrifuged three times with deionized water and alcohol, dried, and finally ground and sieved to obtain SF-HAP powder.

[0056] 19g PLLA powder was dispersed in 500mL anhydrous ethanol and ultrasonically treated for 1 hour at an ultrasonic temperature of 25°C to obtain a PLLA suspension; 3g SF-HAP powder was dispersed into the PLLA suspension, the ultrasonic dispersion time was 30 minutes, the magnetic stirring dispersion time was 3 hours, and the magnetic stirring time was 25°C to obtain a uniformly dispersed PLLA / SF-HAP mixed suspension; and then centrifuged for 1 hour at a centrifugal speed of 1200r / min, a drying time of 24 hours, and a powder grinding and drying time of 10 minutes to obtain a PLLA / SF-HAP composite powder.

[0057] The PLLA / SF-HAP composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold are as follows: preheating the powder to a temperature slightly lower than the melting point; flattening the rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA / SF-HAP bioscaffold, recorded as 15wt% PLLA / SF-HAP, and the main process parameters are: laser power of 1.2W, scanning spacing of 0.4mm, scanning speed of 80m / s, spot diameter of 400mm, and powder bed preheating temperature of 150°C.

[0058] In this example, in the cell experiment, tumor cells were cultured in the PLLA / SF-HAP composite bioscaffold, and the ratio of live cells to dead cells was 0:100, and no cells survived, which proved that it had a good anti-tumor effect. At the same time, it was stained with ROS fluorescence, and it was found that a large amount of ROS was produced.

[0059] In this example, the PLLA / SF-HAP scaffold consumed H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 60% decrease in the absorbance of MB at 663 nm.

[0060] In this example, the PLLA / SF-HAP scaffold consumed GSH to generate superoxide radicals after 2.5 hours, resulting in a 60% decrease in the absorbance of DPBF at 412 nm.

[0061] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 25%.

[0062] In this example, after immersion in simulated body fluid for 28 days, the Fe 3+ The release amount reaches 20%.

[0063] In this example, after immersion in simulated body fluid for 28 days, the SeO3 2- The release amount reached 24%.

[0064] Comparative Example 1

[0065] 20g PLGA powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold were as follows: preheating the powder to a temperature slightly below the melting point; flattening a rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA bioscaffold, recorded as 0wt% PLLA / SF-HAP. The main process parameters were: laser power of 1.0W, scanning spacing of 0.4mm, scanning speed of 100m / s, spot diameter of 400mm, and powder bed preheating temperature of 150°C.

[0066] In this example, in the cell experiment, tumor cells were cultured on the PLLA / HAP composite bioscaffold, and the ratio of live cells to dead cells was 98:2. A large number of cells survived, proving that it did not have a good anti-tumor effect. At the same time, ROS fluorescence staining was used to find that no ROS was generated.

[0067] In this example, the PLLA / HAP scaffold did not consume H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 3% decrease in the absorbance of MB at 663 nm.

[0068] In this example, the PLLA / SF-HAP scaffold did not consume GSH to generate superoxide radicals after 2.5 hours, resulting in a 3% decrease in the absorbance of DPBF at 412 nm.

[0069] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 6%.

[0070] Comparative Example 2

[0071] SF-HAP nanoparticles were synthesized by chemical coprecipitation method. Ca(NO3)2, (NH4)2HPO4, FeCl3 and Na2SeO3 were donors of Ca, P, Fe and Se, respectively. First, polyethylene glycol (PEG, 0.2 g) was used as a dispersant to prepare a mixed solution of Ca(NO3)2 (0.5 M) and FeCl3 (0.2 M) at 60°C with vigorous stirring. During the reaction, the pH value was kept at around 11 by dropping ammonium hydroxide. Similarly, a mixed solution of (NH4)2HPO4 (0.3 M) and Na2SeO3 (0.45 M) was prepared. Subsequently, the (P+Se) solution was added dropwise to the (Ca+Fe) solution under vigorous stirring. Then, the obtained solution was stirred for 3 hours. The aged precipitate was centrifuged three times with deionized water and alcohol, dried, and finally ground and sieved to obtain SF-HAP powder.

[0072] 18.5g PLLA powder was dispersed in 400mL anhydrous ethanol and ultrasonically treated for 0.5 hours at a temperature of 30°C to obtain a PLGA suspension; 1.5g SF-HAP powder was dispersed in the PLLA suspension, the ultrasonic dispersion time was 40 minutes, the magnetic stirring dispersion time was 6 hours, and the magnetic stirring time was 30°C to obtain a uniformly dispersed BaTiO3-GO / PLGA mixed suspension; then centrifugal treatment was performed, the centrifugal time was 0.5 hours, the centrifugal speed was 2000r / min, the drying time was 9 hours, and the powder time after grinding and drying was 5 minutes to obtain a PLLA / SF-HAP composite powder.

[0073] The PLLA / SF-HAP composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold are as follows: preheating the powder to a temperature slightly lower than the melting point; flattening a rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA / SF-HAP bioscaffold, recorded as 7.5wt% PLLA / SF-HAP, and the main process parameters are: laser power of 2.0W, scanning spacing of 0.5mm, scanning speed of 200m / s, spot diameter of 500mm, and powder bed preheating temperature of 155℃.

[0074] In this example, in the cell experiment, tumor cells were cultured in the PLLA / SF-HAP composite bioscaffold, and the ratio of live cells to dead cells was 0:100. A large number of cells survived, proving that it has a good anti-tumor effect. At the same time, it was stained with ROS fluorescence, and it was found that a large amount of ROS was produced.

[0075] In this example, the PLLA / SF-HAP scaffold consumed H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 23% decrease in the absorbance of MB at 663 nm.

[0076] In this example, the PLLA / SF-HAP scaffold did not consume GSH to generate superoxide radicals after 2.5 hours, resulting in a 23% decrease in the absorbance of DPBF at 412 nm.

[0077] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 16%.

[0078] Comparative Example 3

[0079] SF-HAP nanoparticles were synthesized by chemical coprecipitation method. Ca(NO3)2, (NH4)2HPO4, FeCl3 and Na2SeO3 were donors of Ca, P, Fe and Se, respectively. First, polyethylene glycol (PEG, 0.2 g) was used as a dispersant to prepare a mixed solution of Ca(NO3)2 (0.5 M) and FeCl3 (0.2 M) at 60°C with vigorous stirring. During the reaction, the pH value was kept at around 11 by dropping ammonium hydroxide. Similarly, a mixed solution of (NH4)2HPO4 (0.3 M) and Na2SeO3 (0.45 M) was prepared. Subsequently, the (P+Se) solution was added dropwise to the (Ca+Fe) solution under vigorous stirring. Then, the obtained solution was stirred for 3 hours. The aged precipitate was centrifuged three times with deionized water and alcohol, dried, and finally ground and sieved to obtain SF-HAP powder.

[0080] 15g PLLA powder was dispersed in 500mL anhydrous ethanol and ultrasonically treated for 1 hour at an ultrasonic temperature of 25°C to obtain a PLLA suspension; 5g SF-HAP powder was dispersed into the PLLA suspension, the ultrasonic dispersion time was 20 minutes, the magnetic stirring dispersion time was 3 hours, and the magnetic stirring time was 30°C to obtain a uniformly dispersed PLLA / SF-HAP mixed suspension; and then centrifuged for 1.5 hours, a centrifugal speed of 1500r / min, a drying time of 10 hours, and a powder grinding and drying time of 6 minutes to obtain a PLLA / SF-HAP composite powder.

[0081] The PLLA / SF-HAP composite powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a bioscaffold. The steps for preparing the bioscaffold were as follows: preheating the powder to a temperature slightly lower than the melting point; flattening a rod to spread the powder; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PLLA / SF-HAP bioscaffold, recorded as 25wt% PLLA / SF-HAP. The main process parameters were: laser power of 1.5W, scanning spacing of 0.6mm, scanning speed of 200m / s, spot diameter of 600mm, and powder bed preheating temperature of 145°C.

[0082] In this example, in the cell experiment, tumor cells were cultured in the PLLA / SF-HAP composite bioscaffold, and the ratio of live cells to dead cells was 0:100. A large number of cells survived, proving that it has a good anti-tumor effect. At the same time, it was stained with ROS fluorescence, and it was found that a large amount of ROS was produced.

[0083] In this example, the PLLA / SF-HAP scaffold consumed H2O2 to generate hydroxyl radicals after 2.5 hours, resulting in a 28% decrease in the absorbance of MB at 663 nm.

[0084] In this example, the PLLA / SF-HAP scaffold did not consume GSH to generate superoxide radicals after 2.5 hours, resulting in a 28% decrease in the absorbance of DPBF at 412 nm.

[0085] In this example, after being immersed in simulated body fluid for 28 days, the mass loss of the PLLA / SF-HAP scaffold reached 19%.

Claims

1. A selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and a preparation method thereof, characterized in that: The following steps are involved: S1. SeO3 is prepared by coprecipitation 2- and Fe 3+ Doped into hydroxyapatite (HAP) to obtain SF-HAP powder; S2, dispersing PLLA powder in anhydrous ethanol to obtain a PLLA suspension, and then dispersing SF-HAP powder into the PLLA suspension to obtain a PLLA / SF-HAP mixed suspension, and subjecting the suspension to ultrasonication, magnetic stirring, centrifugation, drying, grinding and other steps to obtain a PLLA / SF-HAP composite powder; S3. Prepare PLLA / SF-HAP scaffold by selective laser sintering technology using PLLA / SF-HAP composite powder.

2. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 1, characterized in that: In step S1, a synthetic HAP solution is prepared to obtain SF-HAP powder, and the steps are as follows: S11, dispersing calcium nitrate pentahydrate in deionized water and ultrasonically treating it, adding polyethylene glycol to disperse it to prepare a calcium nitrate solution, stirring and reacting it at 60° C. for 30 minutes, and adding ammonia water to adjust the pH; S12, dissolving diammonium hydrogen phosphate in deionized water, adjusting the pH with ammonia water, and then ultrasonically treating; The diammonium hydrogen phosphate solution was slowly added dropwise to the calcium nitrate solution, and after stirring at 60°C for 3 hours, the supernatant was taken, and the solution was repeatedly washed by centrifugation with deionized water and ethanol, and the product was placed in a vacuum oven to dry to obtain HAP powder; S13. The synthesis process of SF-HAP powder is as follows: in the above-mentioned process of synthesizing HAP, sodium selenite is additionally added to diammonium hydrogen phosphate, and ferric chloride is additionally added to calcium nitrate, and other reaction conditions remain unchanged, to finally obtain SF-HAP powder.

3. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 2, characterized in that: In the step S11, the molecular weight of the selected dispersant polyethylene glycol is 6000.

4. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 2, characterized in that: In step S11, the alkaline pH of the solution is greater than 10.

5. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 1, characterized in that: In step S1, the molar ratio of calcium nitrate to ferric chloride is in the range of 7:2-7:

4.

6. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 2, characterized in that: In step S13, the molar ratio of diammonium hydrogen phosphate to sodium selenite is in the range of 1:3-2:

3.

7. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 1, characterized in that: In step S2, the dispersion method is ultrasound and magnetic stirring. The ultrasonic dispersion time is 10-60 minutes and the temperature is 20-50°C; the magnetic stirring dispersion time is 0.5-6 hours, the speed is 300-800r / min, and the temperature is 30-60°C.

8. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and the preparation method thereof according to claim 1, characterized in that: In the step S2, the particle size of PLLA is 0.1-5 um, and the purity is greater than 99%.

9. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and preparation method thereof according to claim 1, characterized in that: In the step S3, in the PLLA / SF-HAP bioscaffold, the mass fraction of SF-HAP is 5-30%, and the mass fraction of PLLA is 70-95%.

10. The selenium-iron co-doped hydroxyapatite reinforced polylactic acid scaffold and the preparation method thereof according to claim 1, characterized in that: In step S3, the PLLA / SF-HAP composite powder is placed in a 3D printing system, and sintered layer by layer according to the slice information of the three-dimensional bracket model. The steps of preparing the bracket are: preheating the powder, spreading the powder by a roller, sintering the powder layer by layer with a laser beam, and removing excess powder after sintering to obtain a composite bracket. The process parameters of selective laser sintering are: laser power of 0.5-4W, scanning spacing of 0.2-1.0mm, scanning speed of 50-200m / s, and powder bed preheating temperature of 140-160°C.